Sports Beyond Competition–Empowering Youth and Building National Integrity - Soumya N. Gudi, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Sports are not just entertainment activities; they are efficient and powerful cultural instruments which shape individuals and societies. This paper studies various situations how sports empower youth and build national integration. It highlights how practicing sports promotes life skills, stimulates diversity, and creates harmony across the cultural, ethnic, and social divides. Study findings indicates that how sports help youth to overcome challenges in society and enhances their self-esteem, discipline and leadership quality among the youth of nation. However, challenges include poor infrastructure, unfair access, cultural biases hamper their abilities. The study makes an argument that well designed and organised programmes and long-lasting sports events integrated into society and empower youth and forging national cohesion.
Keywords: Youth Empowerment; Sports Participation; National Integration; Social Inclusion; Life Skills